Measure of Early Vision Use: development of a new assessment tool for children with cerebral palsy. Issue 15 (17th July 2022) - Deramore Denver, Belinda; Froude, Elspeth; Rosenbaum, Peter; Imms, Christine
Abstract: Purpose: To report the development of an assessment tool to describe "how vision is used" for children with cerebral palsy. Method: Measurement development consisted of three steps: (i) an online survey to explore the relevance and comprehensiveness of visual behaviours identified in a previous conceptualisation study; (ii) construction of items and a rating scale for the new measure; and (iii) cognitive interviews to explore comprehensibility and refine the measure in preparation for field testing. Survey respondents were 130 parents of children with cerebral palsy, eight adults with cerebral palsy, and 108 clinicians ( n = 246). Nine parents participated in the interviews. Results: The new tool, the Measure of Early Vision Use, is a 14-item descriptive measure of typical performance of visual behaviours observable in everyday activities, as rated by parent/caregiver observation. Each item is rated on a 4-point ordinal scale. Conclusions: This new measure is conceptually grounded within the Activity level domain of the International Classification of Functioning, Disability and Health as a measure of a single visual ability construct. The target population is children with cerebral palsy, and using parent report the Measure of Early Vision Use describes both strengths and limitations in using vision. This study addressed the selection of items and response options for the new scale, and provides evidence to support content relevance, comprehensiveness and comprehensibility from key stakeholders. Further research will explore psychometric properties and clinical utility. Implications for rehabilitation: The ability to use vision in daily activities is relevant to the development and learning of all children, so the availability of a method for describing visual abilities has potential for diverse research and clinical purposes. The Measure of Early Vision Use is a parent-report tool that provides a criterion-referenced method for quantifying and describing how children use vision in typical daily activities to support intervention planning. Clinicians and parents wishing to measure vision use in children with cerebral palsy can be confident about the rigorous methods used to develop this tool, including consultation with key stakeholders.